GABA-A channel subunit expression in human glioma correlates with tumor histology and clinical outcome. - Anja Smits (Public Library of Science (PLoS), 2012)
GABA (γ-aminobutyric acid) is the main inhibitory neurotransmitter in the CNS and is present in high concentrations in presynaptic terminals of neuronal cells. More recently, GABA has been ascribed a more widespread role in the control of cell proliferation during development where low concentrations of extrasynaptic GABA induce a tonic activation of GABA receptors. The GABA-A receptor consists of a ligand-gated chloride channel, formed by five subunits that are selected from 19 different subunit isoforms. The functional and pharmacological properties of the GABA-A channels are dictated by their subunit composition. Here we used qRT-PCR to compare mRNA levels of all 19 GABA-A channel subunits in samples of human glioma (n = 29) and peri-tumoral tissue (n = 5). All subunits except the ρ1 and ρ3 subunit were consistently detected. Lowest mRNA levels were found in glioblastoma compared to gliomas of lower malignancy, except for the θ subunit. The expression and cellular distribution of the α1, γ1, ρ2 and θ subunit proteins was investigated by immunohistochemistry on tissue microarrays containing 87 gliomas grade II. We found a strong co-expression of ρ2 and θ subunits in both astrocytomas (r = 0.86, p<0.0001) and oligodendroglial tumors (r = 0.66, p<0.0001). Kaplan-Meier analysis and Cox proportional hazards modeling to estimate the impact of GABA-A channel subunit expression on survival identified the ρ2 subunit (p = 0.043) but not the θ subunit (p = 0.64) as an independent predictor of improved survival in astrocytomas, together with established prognostic factors. Our data give support for the presence of distinct GABA-A channel subtypes in gliomas and provide the first link between specific composition of the A-channel and patient survival.